Impact of nitrogen and sulphur fertilization on the growth and micronutrient content of spring wheat (Triticum aestivum L.) - Juhász, Evelin Kármen; Balláné Kovács, Andrea (Acta Agraria Debreceniensis, 2018)
Micronutrients are as important as macronutrients for crops. Each micronutrient has its own function in plant growth. Zinc is important for membrane integrity and phytochrome activities. Copper is an essential micronutrient required for the growth of wheat. Manganese is required for enzyme activation, in electron transport, and in disease resistance. The pot experiment was set up in greenhouse on calcareous chernozem soil Debrecen-Látókép with a spring wheat. In certain development stages (according to BBCH growth scale of wheat), at the beginning of stem elongation (29–30), at the heading (51–59), at the flowering (61–69) stage three average plants were removed from all pots for analysis. Fresh and dry weight of the plant samples were measured. Plant leaves after drying were digested by HNO3-H2O2 methods and manganese, zinc and copper contents of plant were quantified by atomic absorption spectrophotometry. At the flowering stage, when the nutrient uptake of plants is the most intensive, the weight of wheat ranged between 0.94–1.57 g plant-1. In this development stage, the NS2 treatment produced the highest weight of wheat, and compared to this the NS3 treatment decreased that value already. The results show unfavourable effect of NS3 treatment. On the basis of microelement content of wheat and the weight of a plant, nutrient uptake by plant were calculated. At the beginning of growth the starter treatment had positive effect on Cu-uptake compared to the NS1 treatment, where the same dose of fertilizer was stirred into the soil. Wheat is very sensitive to copper deficiency, so copper dissolved by starter treatment could be favourable to the early development of wheat. At flowering stage the Zn-uptake of wheat became the highest and it was between 133.7–234.6 mg plant-1. The Mn-uptake of wheat plant was higher than the Cu- and Zn-uptake of wheat. This phenomenon can be explained by the fact that the untreated soil had higher Mn-content, than Cu- and Zn-content. To summarize the results, it can be stated, that the copper uptake of wheat was more affected by the different treatments in the stage of stem elongation, while Mn- and Zn-uptake of wheat were influenced primarily in the stage of heading and flowering.